First Principle Study of Phosphorus Nanotube: Structural, Mechanical and Electronic Properties (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Discovery of fullerene and other Nano-dimensional allotropes of carbon revolutionized the technology. Their properties were very different and interesting from their bulk counter parts. This made scientists to search for other materials, which are similar to graphite. In this quest, they searched many-layered structure like silicon, germanium, black phosphorus etc. In this research, first principle simulation based on density functional theory has been used with siesta performance to investigate structural, mechanical and electronic properties of the different geometrical phosphorus nanotubes. To performcalculation double zeta polarized basis set and generalized gradient approximation as exchange correlation energy functional have been used. After the calculation, we found three phosphorus nanotubes with different geometrical shapes armchair, zigzag and helical with different bods’ length. Mechanical property of the each tube shows that mechanical strength of the armchair nanotube is comparatively high than other two zigzag and armchair nanotubes. Electronic properties of the nanotubes clearly indicate that they are semiconducting in nature and their properties depends on their chirality.